2012
DOI: 10.1021/am3015197
|View full text |Cite
|
Sign up to set email alerts
|

Boron Subphthalocyanines as Organic Electronic Materials

Abstract: Boron subphthalocyanines (BsubPcs) are an emerging class of high performing materials in organic electronics. Since the first use of chloroboron subphthalocyanine in an organic electronic device 6 years ago subphthalocyanines have shown potential as functional materials in organic light emitting diodes (OLEDs) and organic photovoltaics (OPVs). Here we review the material properties of chloroboron subphthalocyanine (Cl-BsubPc) and its use as an organic semiconductor. We then highlight our efforts toward derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
181
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(207 citation statements)
references
References 115 publications
1
181
0
1
Order By: Relevance
“…As will be discussed in more detail in section 4.2, detection in our TPPE spectrum results from autoionization into the continuum supported above the local vacuum level of islands of ClBSubPc/Cu(111). All observed attributes of the state labeled "f-LUMO" suggest strongly that this state is formed by partial electron transfer from Cu(111) to a previously unoccupied state of the molecule: i) The peak center is very close to E F , with E F bisecting the peak; ii) assignment of this feature as HOMO is incompatible with an ionization energy of approximately 6 eV reported previously on Ag(111) [31] and measured by us on graphite, given a global work function below 4.5 eV; iii) the solution HOMO-LUMO gap of ~2.2 eV [40] predicts to first approximation a LUMO energy near E F ; iv) the localized, non-dispersive electronic character is indicative of a molecular level; and v) the disappearance of this peak at coverages r 1 MLE is expected for an interface-specific feature arising from charge-transfer from the surface to a molecule. Given this interpretation of the "f-LUMO", the binding energy of -0.03(2) eV at k || = 0 implies transfer of close to a full electron to the molecule and is presumably accompanied by backdonation to lower lying molecular orbitals [41].…”
Section: Excited Statesmentioning
confidence: 62%
See 1 more Smart Citation
“…As will be discussed in more detail in section 4.2, detection in our TPPE spectrum results from autoionization into the continuum supported above the local vacuum level of islands of ClBSubPc/Cu(111). All observed attributes of the state labeled "f-LUMO" suggest strongly that this state is formed by partial electron transfer from Cu(111) to a previously unoccupied state of the molecule: i) The peak center is very close to E F , with E F bisecting the peak; ii) assignment of this feature as HOMO is incompatible with an ionization energy of approximately 6 eV reported previously on Ag(111) [31] and measured by us on graphite, given a global work function below 4.5 eV; iii) the solution HOMO-LUMO gap of ~2.2 eV [40] predicts to first approximation a LUMO energy near E F ; iv) the localized, non-dispersive electronic character is indicative of a molecular level; and v) the disappearance of this peak at coverages r 1 MLE is expected for an interface-specific feature arising from charge-transfer from the surface to a molecule. Given this interpretation of the "f-LUMO", the binding energy of -0.03(2) eV at k || = 0 implies transfer of close to a full electron to the molecule and is presumably accompanied by backdonation to lower lying molecular orbitals [41].…”
Section: Excited Statesmentioning
confidence: 62%
“…for PTCDA, C 60 , and several other organic molecules on coinage metal surfaces [26,31,35,40,[42][43][44][45][46]. In the case of ClB-SubPc on Ag(111), Berner et al inferred a partial charge transfer from surface to molecule from analysis of XPS and UPS [31].…”
Section: Summary Ofmentioning
confidence: 99%
“…[3] The interest to subphthalocyanines is strongly connected with perspectives of their applications in organic photovoltaics and electronics. [4] They exhibit good performance as donor [5] or acceptor [6] layers in hybride organic solar cells, as hole transporter in perovskite solar cells. [7] Recently it was shown that subphthalocyanines can be used in fullerenefree organic photovoltaics.…”
mentioning
confidence: 99%
“…[18] Porphyrazines with annulated 1,2,5-chalcogenadiazole rings are known as strongly electron-deficient phthalocyanine analogues [19][20][21] which can be considered as perspective functional materials for design of organic electronic devices. Thus, tetra(1,2,5-thiadiazolo) porphyrazine, [(SN 2 ) 4 PAH 2 ], and its metal complexes [(SN 2 ) 4 PAM] (M=Zn II , V IV O, and Fe II ) were used as n-type organic semiconductors in the prototypes of field-effect transistors and photovoltaic cells by Awaga and co-workers [22] and in our works. [18,23] The 1,2,5-thiadiazole-fused porphyrazine macrocycle exhibits even stronger p-electron-acceptor properties in complexes with the IIIA group metals [(SN 2 ) 4 PAM] (M = Al III Cl, Ga III Cl, In III OAc).…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8] Reflecting the bipolar nature, 8 SubPc can be used even as a donor material in heterojunction OSCs with C 60 as an acceptor. 9,10 Especially, the bipolar nature of SubPc and SubNc enables cascade heterojunction OCSs, 3,[5][6][7] whose PCEs reach to 8.4%. 3 However, the carrier injection dynamics in the heterojunction OSCs with bipolar molecule remains unclear.…”
mentioning
confidence: 99%